Prevention of peri-interventional hypothermia during endoscopic retrograde cholangiopancreatography using a forced-air heating system - Stahl, Klaus; Schuette, Eloise; Schirmer, Paul; Fuge, Jan; Weber, Anna-Lena; Heidrich, Benjamin; Schneider, Andrea; Pape, Thorben; Krauss, Terence; Wedemeyer, Heiner; Lenzen, Henrike (Endoscopy International Open, 2024)
Background and study aims Perioperative hypothermia is associated with significant complications and can be prevented with forced-air heating systems (FAHS). Whether hypothermia occurs during prolonged endoscopic sedation is unclear and prevention measures are not addressed in endoscopic sedation guidelines. We hypothesized that hypothermia also occurs in a significant proportion of patients undergoing endoscopic interventions associated with longer sedation times such as endoscopic retrograde cholangiopancreaticography (ERCP), and that FAHS may prevent it.Patients and methods In this observational study, each patient received two consecutive ERCPs, the first ERCP following current standard of care without FAHS (SOC group) and a consecutive ERCP with FAHS (FAHS group). The primary endpoint was maximum body temperature difference during sedation.Results Twenty-four patients were included. Median (interquartile range) maximum body temperature difference was −0.9°C (−1.2; −0.4) in the SOC and −0.1°C (−0.2; 0) in the FAHS group (P < 0.001). Median body temperature was lower in the SOC compared with the FAHS group after 20, 30, 40, and 50 minutes of sedation. A reduction in body temperature of > 1°C (P < 0.001) and a reduction below 36°C (P = 0.01) occurred more often in the SOC than in the FAHS group. FAHS was independently associated with reduced risk of hypothermia (P = 0.006). More patients experienced freezing in the SOC group (P = 0.004). Hemodynmaic and respiratory stability were comparable in both groups.Conclusions Hypothermia occurred in the majority of patients undergoing prolonged endoscopic sedation without active temperature control. FAHS was associated with higher temperature stability during sedation and better patient comfort.
Keywords: Benign strictures; ERC topics; Sedation and monitoring